Molecular determinants of response to neoadjuvant pembrolizumab plus chemotherapy in patients with high-risk, early-stage, triple-negative breast cancer: exploratory analysis of the open-label, multicohort phase 1b KEYNOTE-173 study - Rebecca Dent; Javier Cortés; Yeon Hee Park; Eva Muñoz-Couselo; Sung-Bae Kim; Joohyuk Sohn; Seock-Ah Im; Esther Holgado; Theodoros Foukakis; Sherko Kümmel; Jennifer Yearley; Anran Wang; et al. (Breast Cancer Research)
Abstract Background The multicohort, open-label, phase 1b KEYNOTE-173 study was conducted to investigate pembrolizumab plus chemotherapy as neoadjuvant therapy for triple-negative breast cancer (TNBC). This exploratory analysis evaluated features of the tumor microenvironment that might be predictive of response. Methods Cell fractions from 20 paired samples collected at baseline and after one cycle of neoadjuvant pembrolizumab prior to chemotherapy initiation were analyzed by spatial localization (tumor compartment, stromal compartment, or sum of tumor and stromal compartments [total tumor]) using three six-plex immunohistochemistry panels with T-cell, myeloid cell, and natural killer cell components. Area under the receiver operating characteristic curve (AUROC) was used to assess associations between immune subsets and gene expression signatures (T-cell–inflamed gene expression profile [TcellinfGEP] and 10 non-TcellinfGEP signatures using RNA sequencing) and pathologic complete response (pCR). Results At baseline, six immune subsets quantitated within the tumor compartment showed AUROC with 95% CIs not crossing 0.5, including CD11c+ cells (macrophage and dendritic cell [DC]: AUROC, 0.85; 95% confidence interval [CI] 0.63–1.00), CD11c+/MHCII+/CD163−/CD68− cells (DC: 0.76; 95% CI, 0.53–0.99), CD11c+/MHCII−/CD163−/CD68− cells (nonactivated/immature DC: 0.80; 95% CI 0.54–1.00), and CD11c+/CD163+ cells (M2 macrophage: 0.77; 95% CI 0.55–0.99). Other associations with pCR included baseline CD11c+/MHCII−/CD163−/CD68− (nonactivated/immature DC) within the total tumor (AUROC, 0.76; 95% CI 0.51–1.00) and the baseline CD11c/CD3 ratio within the tumor compartment (0.75; 95% CI 0.52–0.98). Changes in immune subsets following one cycle of pembrolizumab were not strongly associated with pCR. Although T-cell associations were relatively weak, specific CD8 subsets trended toward association. The AUROC for discriminating pCR based on TcellinfGEP was 0.55 (95% CI 0.25–0.85); when detrended by TcellinfGEP, AUROC varied for the non-TcellinfGEP signatures. TcellinfGEP expression trended higher in responders than in nonresponders when evaluating pCR. Conclusions Myeloid cell populations within the tumor compartment at baseline and TcellinfGEP show a promising trend toward an association with pCR in a small subgroup of patients with early-stage TNBC treated with neoadjuvant pembrolizumab plus chemotherapy. Trial registration ClinicalTrials.gov, NCT02622074; registration date, December 2, 2015.